Wechsler Adult Intelligence Scale‐III profile in the early stages of Alzheimer's disease: performance in subtests sensitive to and resistant to normal decline with ageing. Issue 1 (17th December 2014) - Matsuda, Osamu; Saito, Masahiko; Kato, Mayumi; Azami, Hiroki; Shido, Emi
Abstract Aim This study examined the significance of age‐related subtest scores from the Japanese version of the Wechsler Adult Intelligence Scale‐III in patients in the early stages of Alzheimer's disease (AD). Methods The subjects of this study included 58 elderly Japanese persons classified into two groups: AD group (n = 29) and control group (n = 29). These groups did not differ in age, years of education, gender ratio, Hasegawa's Dementia Scale‐Revised score, or Full‐Scale IQ score. No subject scored below the cut‐off point on Hasegawa's Dementia Scale‐Revised, a frequently used dementia screen test in Japan. Results At the index score level, General Ability Index scores were the only scores that differed significantly between the groups, with the AD group scoring significantly lower than the control group (P < 0.05, Hedges' g = 0.54). At the subtest level, information scores were the only scores that differed significantly between the groups, with the AD group significantly lower than the control group (P < 0.01, Hedges' g = 0.74). Conclusion The General Ability Index is a composite score that deducts components of working memory and processing speed, which are sensitive to decline with normal ageing, from the Full‐Scale IQ. It also served as a subtest measuring crystallized intelligence, especially of acquired knowledge of general and factual information. Therefore, the results of this study seem to suggest that Wechsler Adult Intelligence Scale‐III profile of very early AD may be characterized by weak performance on subtests normally resistant to decline with ageing.